Developing a Generic Augmented-Reality Interface - Poupyrev, Ivan; Tan, Desney; Billinghurst, Mark; Kato, Hirokazu; Regenbrecht, Holger; Tetsutani, Nobuji (IEEE Computer, 2002)
The Tiles system seamlessly blends virtual and physical objects to create a work space that combines the power and flexibility of computing environments with the comfort and familiarity of the traditional workplace.